2003
DOI: 10.3171/jns.2003.99.2.0248
|View full text |Cite
|
Sign up to set email alerts
|

Smaller cerebral aneurysms producing more extensive subarachnoid hemorrhage following rupture: a radiological investigation and discussion of theoretical determinants

Abstract: Smaller cerebral aneurysm size is associated with a larger volume of SAH. The pathophysiological basis for this correlation remains speculative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Though this may be somewhat counterintuitive, it is not unlikely. Previous studies have reported that very small aneurysms are associated with more extensive hemorrhage, 30,33,37,43 are more difficult to treat, are associated with a relatively higher risk of periprocedural complications, particularly when treated endovascularly, and have relatively higher morbidity and mortality. 1,27,36,40 Giant aneurysms may present similar challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Though this may be somewhat counterintuitive, it is not unlikely. Previous studies have reported that very small aneurysms are associated with more extensive hemorrhage, 30,33,37,43 are more difficult to treat, are associated with a relatively higher risk of periprocedural complications, particularly when treated endovascularly, and have relatively higher morbidity and mortality. 1,27,36,40 Giant aneurysms may present similar challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we determined the percentages of carotid and basilar bifurcation aneurysms in the group of unruptured aneurysms. Finally, we calculated the number of carotid bifurcation aneurysms versus basilar in the ruptured as well as unruptured group of aneurysms based on the data derived from all studies except the one that did not specify the number of aneurysms at both locations [8]. Since the subset of data used in this analysis exists only of basilar and carotid artery bifurcation aneurysms and the normal configuration of the circle of Willis holds 2 ICA bifurcations and only 1 BA bifurcation, the expected ratio of aneurysms between both locations (assuming that all other variables are similar at both locations) is 2:1 (or 67:33%) in favor of the carotid artery.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, several previous studies have shown that the decision to treat unruptured aneurysms should not be based on aneurysm size alone. 4,16,20,26,27 In view of these data, if the patient is Ͻ50 years of age, is hypertensive, and harbors multiple aneurysms with diameters of Ն4 mm, surgical or endovascular treatment can reasonably be considered for prevention of future aneurysm rupture. Also, based on our current results, if aneurysm enlargement is documented during follow-up, the aneurysm should be treated with a surgical or an endovascular procedure.…”
Section: Surgical Indications For Incidentally Found Small Unrupturedmentioning
confidence: 99%